Apikal hipertrofik kardiyomiyopatili bir hastada koroner arter ile pulmoner arter arasındaki fistülün perkütan yolla kapatılması - (:unkn) unknown (My University, 2013)
Bu yazıda, perkütan kapatma icin yeterli rimleri (kenarları) olan geniş sekundum tipi atriyal septal defekti (ASD) (26 mm) bulunan hastada, işlem sırasında süperiyor vena kava akımının Atriasept ASD tıkayıcının sağ atriyal diski ile tıkandığı ve bunun üzerine cihazin geri çekildiği olgu sunuldu. Bu cihazın geri çekilmesinden sonra aynı seansta Amplatzer ASD tıkayıcı cihazı vena kava akımını bozmadan yerleştirilmiştir.

Summary A fifty-four-year-old female patient was admitted to our unit with exertional chest pain of six months duration. Transthoracic echocardiography showed apical hypertrophy. Upon further investigation, cardiac magnetic resonance im- aging revealed apical hypertrophic cardiomyopathy. The patient underwent myocardial perfusion scintigraphy which showed anterior ischemia. Coronary angiography revealed an arteriovenous fistula (AVF) from the left anterior descend- ing artery to the pulmonary artery. The patient s chest pain was attributed to a coronary steal syndrome secondary to the coronary AVF. The AVF fistula was closed with a coil and the patient s chest pain improved. In conclusion, coronary steal syndrome may lead to myocardial ischemia in patients with a coronary AVF.
Percutaneous closure of the coronary artery-pulmonary artery fistula in a patient with apical hypertrophic cardiomyopathy
Keywords: Kalp ve Kalp Damar Sistemi